The Components of Management of Job Resources of Generation Y Head Nurses in Private Hospitals - Mulalin, Phonthip; Sritoomma, Netchanok; Singchungchai, Phechnoy (NU Journal of Nursing and Health Sciences, 2024)
This research was study aimed to determine the components of management of job resources of Generation Y head nurses in private hospitals. The sample was selected by simple random sampling by means of drawing lots without returning the lots drawn. The research instrument was a questionnaire of the components of job resource management based on the concept of the Aon Hewitt Research and Consulting Institute. It was divided into two parts; general information part and the components of job resource management part. The content validity index of the questionnaire was 0.86 and the Cronbach’s alpha coefficient was 0.98. Data were analyzed by using descriptive statistics and Exploratory Factor Analysis (EFA) The results showed that components and indicators of management of job resources of Generation Y head nurses consisted of 9 components with 58 indicators. The value of factor loading of each component between .560 - .806 with statistical significance at P value <.05. The sequence of component according to value by factor loading from highest to lowest value were as follows. 1) Career opportunities (factor loading .910); 2) Learning & Development (factor loading .890); 3) Performance management (factor loading .870); 4) Enabling Infrastructure and safety (factor loading .830); 5) Teamwork & collaboration and Empowerment/Autonomy (factor loading .790); 6) Diversity & Inclusion ( factor loading . 710) 7); Communication (factor loading .580); 8) Talent & Staffing (Factor loading .560); 9) Rewards & Recognition (Factor loading .498) This research indicates that Generation Y head nurses in private hospitals should apply all 9 components of resources management to manage at the patient unit levels, especially career opportunities and learning and development for nurses and taking into account for performance management to achieve missions and goals of the patient unit levels.